Digital technologies: using PhET in electrodynamics' teaching (Research, Society and Development, 2020)
The scientific experiments reproduction in the laboratory is often difficult, due to the number of students per class, insufficient equipment or the time incompatibility required to carry out the experiments. On the other hand, the fear of handling electrical circuits is undoubtedly one of the causes of students' low performance in electricity. Given this perspective, we proposed the development of experimental Electrodynamics scripts using PhET (Physics Education Technology Project) virtual simulators as a teaching methodology. The activity aimed to apply simulation as a tool to facilitate learning about how an electrical circuit runs. The proposal was applied to 3rd-year students of the Mining Technical Course at the Federal Institute of Education, Science and Technology of Amapá, and involved interaction in a virtual environment, supported by concepts derived from Vygotsky's perspective. For the construction and analysis of data, bibliographic surveys, data collection through tests, interview script and on-site observation were used. The results obtained indicated good acceptance of the proposal, insofar as the technology use had a transforming meaning in pedagogical practice, that is, PhET was not used to simply reproduce the traditional teaching model, but to create learning situations about Electrodynamics. The activity contributed to strengthening a constructivist view of the learning process, highlighting the strong involvement of students in the knowledge construction by integrating previous ideas into the learning tools.